A Comparison of Conventional and Technology-Mediated Selection Interviews With Regard to Interviewees’ Performance, Perceptions, Strain, and Anxiety - Melchers, Klaus G.; Petrig, Amadeus; Basch, Johannes M.; Sauer, Juergen (Frontiers in Psychology, 2021)
Organizations increasingly use technology-mediated interviews. However, only limited research is available concerning the comparability of different interview media and most of the available studies stem from a time when technology-mediated interviews were less common than in the present time. In an experiment using simulated selection interviews, we compared traditional face-to-face (FTF) interviews with telephone and videoconference interviews to determine whether ratings of interviewees’ performance, their perceptions of the interview, or their strain and anxiety are affected by the type of interview. Before participating in the actual interview, participants had a more positive view of FTF interviews compared to technology-mediated interviews. However, fairness perceptions did not differ anymore after the interview. Furthermore, there were no differences between the three interview media concerning psychological and physiological indicators of strain or interview anxiety. Nevertheless, ratings of interviewees’ performance were lower in the technology-mediated interviews than in FTF interviews. Thus, differences between different interview media can still be found nowadays even though most applicants are much more familiar with technology-mediated communication than in the past. The results show that organizations should take this into account and therefore avoid using different interview media when they interview different applicants for the same job opening.